Swearing System in Melayu Ternate Language: Sociolinguistic Studies - Ety Duwila; Sulmi Magfirah; Ermansyah Malik (CV. Eureka Murakabi Abadi, 2022)
This study aims to depict the swearing system in Ternate Malay language that covers the form, meaning, and function. This research used qualitative research. Research on the swearing system in Ternate Malay language was conducted by a qualitative descriptive method that is trying to describe the forms of swearing in Ternate Malay language. The results show that there are three forms of swearing, namely swearing in the form of words, phrases and clauses. Some of these forms of swearing have references and some on the contrary. Swearing forms that have references are grouped into swearing forms which refer to animals, names of fruits, body defects, circumstances, objects, kinships, and professions. Some forms of swearing seem like greetings, especially those that refer to body defects, but in their utterance, they are conveyed in an angry state with a high tone and such hard pressure which makes them categorized as swearing. The use of these forms of swearing is to express anger, irritation, disappointment, admiration, and to insult or mock the interlocutor. It can be concluded that Swearing itself is a noun which means vile words uttered out of anger.